The anxiety-proficiency relationship and the stability of anxiety: The case of Chinese university learners of English and Japanese - Jin, Yinxing; de Bot, Kees; Keijzer, Merel (Studies in Second Language Learning and Teaching, 2015)
Adopting a longitudinal design, this study investigates the effects of foreign language anxiety on foreign language proficiency over time within English and Japanese learning contexts. It also explores the stability of anxiety in English and Japanese over time and the stability of anxiety across English and Japanese. Chinese university students (N=146), who were simultaneously learning Japanese and English, participated in this study. Data were collected twice over a 2-month interval, using the Foreign Language Classroom Anxiety Scale, the English Proficiency Scale, and the Japanese Proficiency Scale. Results showed that anxiety changes had a significantly negative, but weak, correlation with the development of overall proficiency and the proficiency in sub- skills such as reading or speaking, for both English and Japanese, suggesting the interference of anxiety with proficiency levels. Anxiety in Japanese tended to decrease significantly over time, but no significant change was found for English. Furthermore, no significant difference between anxiety in Japanese and English was found at either testing time.